Fish community of two rural lakes and socio-economic assessment in Bumbung Lima, Kepala Batas - Ismail, Azma Hanim; Mansor, Mashhor; Wan Omar, Wan Maznah (2004)
A preliminary study on the fish community in two rural lakes in Bumbung Lima, Kepala Balas was conducted from May 2003 to November 2003. Species abundance and composition were affected by various factors such as water quality, encroaching of aquatic vegetation and human activities at the study sites. A total of 28 fish species from 10 families were recorded during the study period. Cyprinidae was the dominant family while Puntius schwanenfeldii and P. gonionotus were the most widespread species identified. Socioeconomic studies which include human activities in Bumbung Lima area were reviewed. Field survey using questionnaires have been carried out in an attempt to obtain information on socio-demographic status of the study sites. Results showed that over one-third of the heads of households in Bumbung Lima depended on agriculture for their living which was 36.25% followed by 27.5% were government servants. In terms of education, majority of respondents received their level of education only until secondary school, which was accounted for 50% of overall education. Regarding monthly income, about one-third of the respondent earned below than RM 400 per month (33.75%). Only 18.75% of the respondents obtained a salary above RM 1000 per month, which was comparatively small and thus form only a minor portion of total respondents.